A Novel Way of Real-time Crack Monitoring Based on Quantum Dots. (May 2017) - Yao, Zihao; Yin, Shaofeng; Luan, Weiling; Zhong, Qixin; Zhang, Shaofu
Abstract: Recent discoveries have found that pressure dependence in quantum dots (QDs) doped in epoxy resin will have an obvious influence on the intensity of its photoluminescence (PL). Therefore, it is possible for us to monitor cracks due to the concentration of stress near the cracks when the force is loaded and the residual stress alongside the cracks after the force is unloaded. The measurement of the crack length has a wide range which can vary from dozens of microns to several centimetres. Further experiments were carried out to validate that it is the combination of both the abrupt change of stress in substrate and the interaction between the matrix and QDs that realizes the PL enhancement region near the cracks.